Sponsored Migration : The State and Puerto Rican Postwar Migration to the United States - Melendez, Edgardo (Book collections on Project MUSE., 2017)
Sponsored Migration places Puerto Rico's migration policy in its historical context, examining the central role the Puerto Rican government played in encouraging and organizing migration during the postwar period. Melendez sheds an important new light on the many ways in which the government intervened in the movement of its people: attempting to provide labor to U.S. agriculture, incorporating migrants into places like New York City, seeking to expand the island's air transportation infrastructure, and even promoting migration in the public school system. One of the first scholars to explore this topic in depth, Melendez illuminates how migration influenced U.S. and Puerto Rican relations from 1898 onward.